Seasonal incidence of diamondback moth (Plutella xylostella) (Lepidoptera: Plutellidae) and its parasitoids on cabbage - CHAUBEY, B K; MURTHY, K SRINIVASA (The Indian Journal of Agricultural Sciences, 2023)
The seasonal incidence of diamondback moth (Plutella xylostella) and its parasitoids in relation to climatological factors was studied with staggered sowings of cabbage during the years 2013 and 2014 at the NBAIR research farmat Attur, Bengaluru. The pest population peaked during the early summer, March-April months (342 and 243/60 plants) followed by post rainy season, August-October (184 and 208/60 plants) and was low during the early winter months December-January (65 and 68/60 plants) followed by July-August (98 and 96/60 plants). A maximum temperature of 30-35°C with a relative humidity of 61-75% favoured the buildup of the pest. The larval incidence had significant positive correlation with maximum temperature (r = 0.837; P = 0.01) and with minimum temperature (r = 0.594; P = 0.05). Rainfall and number of sunshine hours had a negative impact. The larval parasitoid Cotesiavestalis and the late larval-pupal parasitoid Oomyzus sokolowskii were found to be predominant during both the years of study. Parasitism by C. vestalis was maximum during August- September months (64.89-82.2%), was low during December-January months (41.5-47.5%). O. sokolowskii prevailed high during December- January months (33.33-37.5%) and low during February - March (8.82-8.75%) and July/August-September (6.25-10.0%). Occurrence of the parasitoids was more at minimum temperature of 16-19oC and maximum temperature of 19-33oC with relative humidity 62.5-73.5%.. Rainfall did not influence the activity of both the parasitoids. The activity of the parasitoids was in accordance with the population density of the pest during the various seasons. Augmentative releases of the parasitoids during the periods of their low incidence would provide for greater suppression of the pest and result inreduced usage of insecticides.